The fit matters: Influence of accelerometer fitting and training drill demands on load measures in rugby league players - McLean, B. D.; Cummins, C.; Conlan, G.; Duthie, G.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine the relationship between drill type and accelerometer-derived loads during various team-sport activities and examine the influence of unit fitting on these loads. Methods: Sixteen rugby league players were fitted with microtechnology devices in either manufacturer vests or playing jerseys before completing standardized running, agility, and tackling drills. Two-dimensional (2D) and 3-dimensional (3D) accelerometer loads (BodyLoad™) per kilometer were compared across drills and fittings (ie, vest and jersey). Results: When fitted in a vest, 2D BodyLoad was higher during tackling (21.5 [14.8] AU/km) than during running (9.5 [2.5] AU/km) and agility (10.3 [2.7] AU/km). Jersey fitting resulted in more than 2-fold higher BodyLoad during running (2D=9.5 [2.7] vs 29.3 [14.8] AU/km, 3D=48.5 [14.8] vs 111.5 [45.4] AU/km) and agility (2D=10.3 [2.7] vs 21.0 [8.1] AU/km, 3D=40.4 [13.6] vs 77.7 [26.8] AU/km) compared with a vest fitting. Jersey fitting also produced higher BodyLoad during tackling drills (2D=21.5 [14.8] vs 27.8 [18.6] AU/km, 3D=42.0 [21.4] vs 63.2 [33.1] AU/km). Conclusions: This study provides evidence supporting the construct validity of 2D BodyLoad for assessing collision/tackling load in rugby league training drills. Conversely, the large values obtained from 3D BodyLoad (which includes the vertical load vector) appear to mask small increases in load during tackling drills, rendering 3D BodyLoad insensitive to changes in contact load. Unit fitting has a large influence on accumulated accelerometer loads during all drills, which is likely related to greater incidental unit movement when units are fitted in jerseys. Therefore, it is recommended that athletes wear microtechnology units in manufacturer-provided vests to provide valid and reliable information.